All‐Inorganic Nanocrystals as a Glue for BiSbTe Grains: Design of Interfaces in Mesostructured Thermoelectric Materials1. (22nd May 2014) - Son, Jae Sung; Zhang, Hao; Jang, Jaeyoung; Poudel, Bed; Waring, Al; Nally, Luke; Talapin, Dmitri V.
Abstract Nano‐ and mesostructuring is widely used in thermoelectric (TE) materials. It introduces numerous interfaces and grain boundaries that scatter phonons and decrease thermal conductivity. A new approach has been developed for the rational design of the interfaces in TE materials by using all‐inorganic nanocrystals (NCs) that serve as a "glue" for mesoscopic grains. For example, circa 10 nm Bi NCs capped with (N2H5)4Sb2Te7 chalcogenidometallate ligands can be used as an additive to BiSbTe particles. During heat treatment, NCs fill up the voids between particles and act as a "glue", joining grains in hot‐pressed pellets or solution‐processed films. The chemical design of NC glue allowed the selective enhancement or decrease of the majority‐carrier concentration near the grain boundaries, and thus resulted in doped or de‐doped interfaces in granular TE material. Chemically engineered interfaces can be used as to optimize power factor and thermal conductivity.